COMPORTAMIENTO DE LOS ESTUDIANTES Y SU INCIDENCIA EN EL RENDIMIENTO ESCOLAR DEL SÉPTIMO AÑO DE LA ESCUELA DE EDUCACIÓN BÁSICA ADOLFO JURADO GONZALEZ DEL CANTÓN VENTANAS PROVINCIA LOS RÍOS 2022- 2023. - ZAMBRANO TROYA GERMANIA YOLANDA (2024)
This research aims to: Establish the factors that influence behavior so that teachers apply teaching strategies and improve their attitudes and academic performance of basic education students at the Adolfo Jurado González school. The first thing to do is; examine the different negative factors that intervene so that students present low academic performance, different sources were investigated about these two variables that are of great importance within the education of students, as well as what strategies contribute to improve teaching and therefore have good academic performance. Regarding the methodology used, the type of research is descriptive. Therefore, to obtain information about the behavior and academic performance of the students, a survey of teachers and students was used, which served to obtain very relevant data. Through the execution proposal, some determinants were identified that influence academic performance to be largely overcome, using strategies that involve motivation, with new learning styles, creating new study spaces, innovative activities, among others. . Indeed, this research covers relevant information about student behavior and academic performance, with useful techniques to apply in classes. In conclusion, to improve student behavior and performance, it is essential that teachers have active participation, with team activities, be flexible, empathetic, offer dynamic environments, among others. Keywords: Behavior, incidence, performance, school students